2019
DOI: 10.21272/mmi.2019.1-13
|View full text |Cite
|
Sign up to set email alerts
|

General Overview to Leadership Theories from a Critical Perspective

Abstract: Leadership still seems to be a popular theme among various disciplines and researchers as it was in the past. A growing body of research has been produced in the leadership field until now. Although increased studies and publications help to build up the leadership theory, leadership theory has not been integrated yet. The theoretical studies related to a specific field in a specific time seem to be useful in related field's advancement. With this rationale in this study, it is aimed to examine the prominent l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 16 publications
0
8
0
2
Order By: Relevance
“…The review by Xie (2019), Yahaya and Ebrahim (2016) and Uslu (2019) also reported that trait research has been reviewed repeatedly by different scholars, for example such as, Lord, De Vader and Alliger and Stogdill. According to Harrison (2018) two reviews by Stogdill are widely compared to find out how the conception of the importance of the nature of a leader evolved over a quarter of a century.…”
Section: Leadershipmentioning
confidence: 99%
See 1 more Smart Citation
“…The review by Xie (2019), Yahaya and Ebrahim (2016) and Uslu (2019) also reported that trait research has been reviewed repeatedly by different scholars, for example such as, Lord, De Vader and Alliger and Stogdill. According to Harrison (2018) two reviews by Stogdill are widely compared to find out how the conception of the importance of the nature of a leader evolved over a quarter of a century.…”
Section: Leadershipmentioning
confidence: 99%
“…In a review by Uslu (2019), various highly significant leadership theories in the field of leadership research were surveyed where there are similarities with TL. The main purpose of the survey was to provide an in -depth review of the concept of leadership that opened up a discussion of human behavior in organizations and management.…”
Section: Leadershipmentioning
confidence: 99%
“…Among the prominent theories that researchers developed according to the contingency viewpoint of leadership are Fielder's Contingency theory and Hersey-Blanchard Situational leadership model (Uslu, 2019). As contingency theories were becoming too complex by linking personality characteristics and styles to the situation of followers and the general organizational context as a method to explain and predict which leadership behaviors would be best in a variety of situations, the leader's moral values and character in addition to his capacity to motivate subordinates to perform to their maximum potential emerged as central themes (Best, 2011).…”
Section: Nature Of Leadershipmentioning
confidence: 99%
“…Leadership can be divided into two categories -First, the Universal theory presents the assumptions that a leader has innate characteristics, a set of congenital and subsequently acquired attributes, and that the effectiveness depends on their behavior. The second is the Contingency theory, which assumes that there is no optimal leadership style and that different situations/circumstances require different leadership styles (Uslu, 2019). These theories should not be confused with other organizational-level phenomena despite influencing other processes centered around other individual actors.…”
Section: Leadership and Teamworkmentioning
confidence: 99%